The Influence of Cash Flow Management (Cash Inflow and Cash Outflow) on Liquidity (Current Ratio and Quick Ratio) in the Food and Beverage Sector of MSMEs in the Greater Jakarta Area - Hanifan, Zakie; Maulana, Hendri; Yudiana, Yudiana (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
Objective: This study aims to examine the effect of cash flow management, proxied by cash inflow and cash outflow, on liquidity, as measured by the current ratio and quick ratio, in Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in the Greater Jakarta area. This study also analyzes the partial and simultaneous effects of both independent variables on the dependent variable. Method – This study uses a quantitative causality design with a survey approach. The study population is MSMEs in the food and beverage sector in Greater Jakarta that have been operating for at least two years. A sample of 100 respondents was selected using a purposive sampling technique based on the criteria of having simple financial records and being willing to be respondents. Primary data was collected through a structured questionnaire that included measurements of cash inflow , cash outflow , current ratio , and quick ratio . Data analysis was carried out using descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression analysis followed by hypothesis testing (t-test, F-test, and coefficient of determination). Results – This study found that partially, cash inflow has a positive and significant effect on the current ratio (B=0.0092; p<0.01) and the quick ratio (B=0.0105; p<0.01). Conversely, cash outflow has a negative and significant effect on the current ratio (B=-0.0074; p<0.01) and the quick ratio (B=-0.0089; p<0.01). Simultaneously, cash inflow and cash outflow together have a significant effect on liquidity with an Adjusted R² value of 0.608 for the current ratio and 0.686 for the quick ratio . These findings indicate that the quick ratio is more responsive to changes in cash flow management than the current ratio in MSMEs in the food and beverage sector in Greater Jakarta